Is Microsatellite Instability Really a Good Prognostic Factor of Colorectal Cancer? - Shin, Ui Sup (The Korean Society of Coloproctology, 2014)
PURPOSE: The aim of this study was to investigate the clinicopathologic features of and the prognosis for colorectal cancers (CRCs) with microsatellite instabilities (MSIs). METHODS: Between 2006 and 2009, genotyping was performed on 245 patients with stage II/III CRCs to establish the MSI status. The clinicopathologic differences and the prognostic value of MSI were analyzed. The median follow-up period was 38 months (range, 7-68 months). RESULTS: Of the total 245 patients, 20 (8.2%) had MSI-high (H) and 225 (91.8%) had MSI-low (L) or stable (S) CRCs. Adjuvant chemotherapies were performed on 101 stage II (87.8%) and 107 stage III patients (82.3%). Patients with MSI-H CRCs more frequently had a family history of colon cancer (10% vs. 2.7%, P = 0.003), more frequently had a cancer located at the proximal colon (90.0% vs. 19.1%, P < 0.0001), and more often showed a mucinous phenotype or poor differentiation (35.0% vs. 7.1%, P = 0.001). Despite less frequent lymph node metastasis (25% vs. 55.6%, P = 0.01), the number of retrieved lymph nodes was higher (26.3 ± 13.1 vs. 20.7 ± 1.2, P = 0.04) in the MSI-H group. The overall survival and the disease-free survival (DFS) did not differ with respect to MSI status. However, in the stage II subgroup, the DFS for patients with MSI-H CRCs was significantly worse (72.2% vs. 90.7%, P = 0.03). The multivariate analysis performed on this subgroup revealed that MSI-H was an independent poor prognostic factor (adjusted hazard ratio, 4.0; 95% confidence interval, 1.0-15.6, P = 0.046). CONCLUSION: MSI-H CRCs had distinct clinicopathologic features, and MSI-H was an independent poor prognostic factor in stage II CRCs. Considering the majority of stage II patients were administrated adjuvant chemotherapy, the efficacy of adjuvant chemotherapy for treating MSI CRCs might be different from that for treating MSI-L/S tumors.